Influences of simple strain path changes on mechanical behaviours of pearlitic steel wire. (February 2015) - Zhao, T. Z.; Zhang, G. L.; Song, H. W.; Cheng, M.; Zhang, S. H.
<x content-type="archive" xml:space="preserve">Abstract</x> The mechanical behaviours of the pearlitic steel wires under simple strain path changes (SSPCs) are investigated, including monotonic, cross and reversal loadings. Both the cross and reversal loadings lead to an apparent softening. Especially during the whole reversal loading, the stress is much lower than before unloading. And it is a function of the pre-strain. Additionally, it is found that the maximum strain increases significantly in reversal loading. The microstructures under different SSPCs are investigated using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), with an aim to reveal the micro-mechanisms of the SSPC effects on the mechanical behaviours.